Correlations between deep convection and lightning activity on a global scale - Ávila, Eldo E. (2010)
Satellite observations of cloud top temperature and lightning flash distribution are used to examine the relationship between deep convection and lightning activity over the tropical regions of the northern and southern hemispheres. In agreement with previous work, the analysis of the results shows that, in the summer of both hemispheres, the lightning activity in continental deep convective storms is more intense than that in marine deep convective storms by a factor of between 7 and 10. Furthermore, it was observed that on average the daily lightning rate per 1°×1° grid cell for the southern hemisphere (SH) is about 20% greater than that of the northern hemisphere (NH), which can be attributed to a larger fractional cover by deep convective clouds in the SH. By using a set of independent indicators, it is shown that deep convection and lightning activity over land are well correlated (with correlation coefficients of 0.8 and 0.6 for NH and SH, respectively). This suggests the capacity for observations to act as a possible method of monitoring continental deep convective clouds, which play a key role in regulating the Earth's climate. Since lightning can be monitored easily from ground networks and satellites, it could be a useful tool for validating the performance of model convective schemes and for monitoring changes in climate parameters.